Annex to: Volcanic Ash Cloud Observation using Ground-based Ka-band Radar and Near-Infrared Lidar Ceilometer during the Eyjafjallajökull eruption - Marzano, Frank S.; Mereu, Luigi; Montopoli, Mario; Cimini, Domenico; Martucci, Giovanni (Annals of Geophysics, 2015)
Volcanic ash plumes are formed during explosive volcanic eruptions. After advection over several thousands of kilometers, volcanic ash particles are highly fragmented, dispersed and aged with micron- sized sorting. This Annex describes the ash microphysical modeling and the simulated radar and lidar signatures. [.]